Honouring Differences in Recovery: Methodological Explorations in Creative Eating Disorder Recovery Research - LaMarre A; Healy-Cullen S; Tappin J; Burns M (MDPI (Basel, Switzerland), 2023)
What would it look like to honour differences in eating disorder recovery? Recoveries from eating disorders and eating distress are enacted in relation to discursive, material, and affective flows that open and constrain different possibilities for differently embodied people. Yet, the pull toward establishing consensus on “what recovery is” continues to dominate the landscape of both qualitative and quantitative eating disorder recovery work. While researchers from a variety of perspectives, disciplines, and methodological traditions have sought to establish consensus on what recovery “is”, a singular definition remains elusive. Indeed, when researchers continue to adopt the same methodologies—which largely emphasize establishing patterns of sameness—the opportunity to dig into contradictions and tensions that enliven recoveries is missed. In this paper, we reflect on our experiences conducting creative, collaborative, generative research to re-write, re-design, re-draw, and otherwise re-imagine recoveries. The knowledge generated in our research is co-constructed with people with living experience of disordered/distressed eating/eating disorders who spoke back to mainstream recovery discourses (e.g., the idea that recovery is about perfection, that recovery is linear, that one is either recovered or not, that the word “recovered” encapsulates the experience, etc.). We engaged with 12 participants: four in an online group workshop and eight in individual online sessions. Participants held a variety of experiences and backgrounds from Canada, the United States, and Aotearoa New Zealand. We explored their journeys into this conversation with us, the meaning of recovery, and their thoughts on what makes recovery im/possible. Participants were offered several options for creative engagement and took up the idea of “creativity” in ways as different as the stories they shared. Participants created collages, short stories, poems, drawings, and told stories about their experiences. Here, we discuss methodological insights gained from asking participants to lead the creative process. We also explore how this project potentially enables different ways of thinking about and doing eating disorder recovery. Delving into the differences in both method and content opens up opportunities to take seriously the different relational, material, and affective constellations of participants’ living experiences of eating distress/disorder “recovery”.
Keywords: eating disorders; recovery; qualitative research; creative methods